Recent Developments in Precious Metals Recovery, Zinc Extraction and Iron Control at the Zinc Plant of the Kidd Metallurgical Division - M. R. Coffin (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Since the plant startup in 1972, the leaching and jarosite precipitation circuits at the zinc plant of the Kidd Metallurgical Division have been reconfigured several times to improve overall performance, and/or to respond to market conditions. For the most part, the circuit changes have been driven by two market factors: the price of zinc and the price of silver. Until recently, circuit modifications undertaken to improve zinc extraction and recovery came at the expense of silver recovery, and vice versa. In 2004, the plant was modified once again to produce a precious metals-bearing residue, but additional leaching circuits were added to ensure that zinc extraction and recovery did not suffer as a consequence. The development of the zinc plant of the Kidd Metallurgical Division is updated in this paper, with a focus on the recent circuit modifications and associated control strategies that were implemented to maximize zinc and precious metals recoveries, and control the quality of the jarosite residue.